(untitled) - Bittinger, Marvin L. (Reading, Mass, 1996)
When the answer at the back of the book is simply not enough, then you need the Student Solutions Manual. With fully worked-out solutions to all odd-numbered text problems, the Student Solutions Manual lets you "learn by example" and see the mathematical steps required to reach a solution. Worked-out problems included in the Solutions Manual are carefully selected from the textbook as representative of each section's exercise sets so you can follow-along and study more effectively. The Student Solutions Manual is simply the fastest way to see your mistakes, improve learning, and get better grades.
Keywords: Algebra,Đại số học